SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN TEKNISI MITRA PSB TERBAIK MENGGUNAKAN SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE (SMART) BERBASIS WEBSITE (STUDI KASUS TELKOM JOMBANG) - Rendy Sahala , Mohammad; Setyo Permadi , Ginanjar (Inovate, 2023)
Employees are one of the company's assets that must also be managed properly, because they play an important role in an existing institution or company. One of them is an employee in the field of PSB partner technicians. Where the task of a PSB partner technician is very important in Telkom Jombang, namely being responsible for carrying out installation, maintenance and repair of fiber optic network integration. So it is important for Telkom Jombang. The data is in the form of Productivity Value, Speed Neatness, Quality, Installation, Responsiveness and Attendance. All data will get weight criteria and later the Company will determine the best new partner based on the Final Utility Value obtained by each employee. With 6 criteria, namely productivity, neatness, speed, quality of installation, responsiveness and attendance, the top 3 results obtained are the best PSB partner technicians, namely the first rank is Alternative-16 with the name IRVAN ADI PRASETIYO with a score of 90, the second rank is Alternative-34 with the name SUHERMAN with a score of 89 and the third rank is Alternative-27 with the name NICO WIJAYA with a scor of 88. Keywords: Employee,The SMART, Decision Support System